TURNING OF AISI 304 AUSTENITIC STAINLESS STEEL - Ozek, Cebeli; Hascalik, Ahmet; Caydas, Ulas; Karaca, Faruk; Unal, Engin (Yildiz Technical Univ, 2006)
This paper presents an experimental investigation of the machining characteristics of AISI 304 austenitic stainless steel in turning process. During experiments, parameters such as cutting speed, feed rate and depth of cut were changed to explore their effect on the surface roughness, tool flank wear and tool - chip interface temperature. Chip forms were determined. Taking into consideration the experimental results, it is found that with increasing cutting speed, tool - chip interface temperature and tool flank wear were decreased. Surface roughness got better with decreasing feed rate and depth of cut.
Keywords: Surface roughness; AISI 304 austenitic stainless steel; process parameters